The Effect of Bending Deformation on Charge Transport and Electron Effective Mass of p‐doped GaAs Nanowires. Issue 8 (9th August 2019) - Zeng, Lunjie; Kanne, Thomas; Nygård, Jesper; Krogstrup, Peter; Jäger, Wolfgang; Olsson, Eva
Abstract : Charge transport in nanowires has been shown to be sensitive to externally applied mechanical stress. Compared to uniaxial deformation, bending deformation introduces both compressive and tensile strain at the same time. The effect of bending strain on charge transport and electronic band structure in semiconductor nanowires is still not well understood. Here, Lunjie Zeng et al. (article no.1900134 ) investigated the effect of bending deformation on individual p ‐GaAs nanowires by using in situ electron microscopy and band structure simulation. The nonlinearity of current‐voltage characteristics of the nanowires increases with bending deformation. However, the band gap of the nanowire does not change. Instead, the nonlinearity can be explained by a shift in the valence band maximum due to the strain. The study advances the understanding of how mechanical strain can be used to fine‐tune the electrical properties of nanomaterials.